2008
DOI: 10.1038/sj.bjp.0707604
|View full text |Cite
|
Sign up to set email alerts
|

Agonist‐selective mechanisms of GPCR desensitization

Abstract: The widely accepted model of G protein-coupled receptor (GPCR) regulation describes a system where the agonist-activated receptors couple to G proteins to induce a cellular response, and are subsequently phosphorylated by a family of kinases called the G protein-coupled receptor kinases (GRKs). The GRK-phosphorylated receptor then acts as a substrate for the binding of a family of proteins called arrestins, which uncouple the receptor and G protein so desensitizing the agonist-induced response. Other kinases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
290
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(301 citation statements)
references
References 86 publications
(105 reference statements)
8
290
2
1
Order By: Relevance
“…We investigated whether long-lasting agonist application could induce desensitization as reported for native GPCRs (27). However, we did not observe desensitization of the FRET response even with glutamate concentration as high as 1 mM and glutamate exposure times up to tens of minutes.…”
mentioning
confidence: 91%
“…We investigated whether long-lasting agonist application could induce desensitization as reported for native GPCRs (27). However, we did not observe desensitization of the FRET response even with glutamate concentration as high as 1 mM and glutamate exposure times up to tens of minutes.…”
mentioning
confidence: 91%
“…Desensitization due to receptor internalization is a common feature of G-protein coupled receptors. 37 In the classic desensitization model, repeated exposure to the ligand initiates receptor desensitization by phosphorylating the receptor, thus preventing the coupling of G-protein and a loss of response (i.e., tachyphylaxis) to receptor activation. 38 Recent studies have reported tachyphylaxis in regards to the permeability response to LPA.…”
Section: Studies By Yanagida K Et Almentioning
confidence: 99%
“…Desensitization is complex and for some receptors (e.g., the μ-opioid receptor) can be mediated by distinct signaling pathways depending upon the identity of the bound agonist. 30 Phosphorylation by PKA, PKC or G protein coupled receptor kinases (GRKs) is involved and can result in uncoupling of the receptor from the downstream G proteins. Endocytic removal of the GPCR from the plasma membrane can also occur: GRKs, recruited by Gβγ, phosphorylate the span the plasma membrane.…”
mentioning
confidence: 99%